PENERAPAN METODE USER CENTERED DESIGN PADA GAME BASED LEARNING TERHADAP MOTIVASI BELAJAR SISWA - Ika Asti Astuti; Suyanto Suyanto; Sukoco Sukoco (Informasi Interaktif, 2017)
One of the problems that occurred in the study is the lack of student motivation. One to increase students' motivation is to use games as learning. GBL is defined as the use of games as a learning method. GBL has the advantage to attract and make someone do something but the drawback of this method is sometimes not aligned with the learning objectives, so this study raised the UCD method to solve the problem. This study describes how to apply the methods of UCD in the GBL. Analysis of the data used is descriptive and qualitative on a Likert scale calculations. The research also involved three experts, namely, education experts as validator materials, expert validator game as a game, as the IT expert validator application design. A total of 58 students from two different schools are also involved to choose the design layout design applications and test game for the measurement of learning motivation. Measurements motivation to learn by comparing between GBL which has been designed with the use of paper based quiz. The measurement results show that the motivation of GBL designed can affect students' motivation compared to the use of PBQ. Keyword: User centered design, game based learning